2006
DOI: 10.1021/cm061258c
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclic Ether and Solvent in a Non-Alkoxide Sol−Gel Synthesis of Yttria-Stabilized Zirconia Nanoparticles

Abstract: The effects of cyclic ether (epoxide versus oxetane), solvent, and drying method were examined for a non-alkoxide sol−gel synthesis of yttria-stabilized zirconia (YSZ). YSZ sol−gel materials, from 3 to 25 mol % Y2O3, were successfully prepared with either propylene oxide (PO) or trimethylene oxide (TMO) in both aqueous and mixed ethanol−water solutions of Zr4+ and Y3+ chlorides. Supercritical drying (aerogels) produced fine, nanoparticulate networks, whereas drying under ambient conditions (xerogels) resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…21 Epoxide-based sol-gel chemistry is a versatile route to synthesize iron oxides 21 25,[30][31][32][33][34] Hydrated metal chlorides are the most common precursors due to their high solubility in alcohols and water, and because chloride anions act on the protonated epoxide via nucleophilic attack to shi the equilibrium of the hydrolysis/condensation reactions. 21 Epoxide-based sol-gel chemistry is a versatile route to synthesize iron oxides 21 25,[30][31][32][33][34] Hydrated metal chlorides are the most common precursors due to their high solubility in alcohols and water, and because chloride anions act on the protonated epoxide via nucleophilic attack to shi the equilibrium of the hydrolysis/condensation reactions.…”
Section: Synthesis Of Vfe 2 O X Aerogelsmentioning
confidence: 99%
“…21 Epoxide-based sol-gel chemistry is a versatile route to synthesize iron oxides 21 25,[30][31][32][33][34] Hydrated metal chlorides are the most common precursors due to their high solubility in alcohols and water, and because chloride anions act on the protonated epoxide via nucleophilic attack to shi the equilibrium of the hydrolysis/condensation reactions. 21 Epoxide-based sol-gel chemistry is a versatile route to synthesize iron oxides 21 25,[30][31][32][33][34] Hydrated metal chlorides are the most common precursors due to their high solubility in alcohols and water, and because chloride anions act on the protonated epoxide via nucleophilic attack to shi the equilibrium of the hydrolysis/condensation reactions.…”
Section: Synthesis Of Vfe 2 O X Aerogelsmentioning
confidence: 99%
“…6(b) also displayed peaks for tetragonal phase, but the observed peaks from 200 to 700 cm −1 were mostly broad and the intensities of the peaks were reduced, which indicates less tetragonal characteristics than the 4YSZ in Fig. 6(a) 41,42 . Also, the broad peak near 646 cm −1 observed in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The EDS analysis was performed with a standard‐less approach and no repetition as well was conducted on samples, which might cause an inaccuracy in this measurement. It has been reported that the amount of yttria‐doping affects the zirconia phase 41,43 . Chervin et al 41 investigated the phase transition of yttria‐stabilized zirconia over the range of 3–25 mol% yttria.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous examples of mixed metal oxide aerogels prepared by epoxide-initiated gelation have been reported in the literature. Solid state electrolyte materials, such as yttria-stabilized zirconia (YSZ), have been prepared using this approach [39,40]. Strontium-doped lanthanum manganite (LSM) materials for use as cathodes in solid oxide fuel cells have also been fabricated using the epoxide method [41].…”
Section: Mixed Metal Oxide and Composite Aerogelsmentioning
confidence: 99%